2010
DOI: 10.1143/jjap.49.06gc01
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large-Area Graphene Using Liquid Gallium and Its Electrical Properties

Abstract: We demonstrated a new process for synthesizing a graphene sheet at the interface between solid amorphous carbon and liquid gallium. The insolubility of carbon in gallium strongly restricted the depth of graphitization, but a multilayered graphene sheet having four to six layers of graphene was produced over the entire area of the interface immediately beneath the liquid gallium. We also demonstrated the operation of an electric-field-effect device fabricated on the multilayered graphene with a back-gated confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports. Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports.…”
Section: B Mechanism Of Ga Evaporation Processcontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports. Previous research has suggested that graphitization occurs at the interface between carbon and liquid Ga, 14,15,19 but we found that during Ga evaporation graphene was formed not only on the SiO 2 layer but also above any dimples on the SiO 2 layer, which is inconsistent with previous reports.…”
Section: B Mechanism Of Ga Evaporation Processcontrasting
confidence: 99%
“…2,8 However, although devices fabricated via this method have been observed on SiC substrates, it can be difficult to transfer them to other substrates such as SiO 2 / Si. 14,15 Using liquid Ga has three main advantages. [9][10][11] However, this requires the transfer of graphene to another substrate 12 or etching of the metal layer.…”
Section: Introductionmentioning
confidence: 99%
“…LM alloy has a relatively low melting point, high surface energy, smooth surface plane, and excellent absorbance of carbon,, which is an indication of its potential to act as a good liquid catalyst for graphitization, as well as a solid metal catalyst that can affect the growth, layer number, and crystallinity of graphene [Eq. ]: trueCH44ptnormalC+40.166667emnormalH20.166667emnormalH2+normalC(graphene)0.166667em0.277778em(Galliumcatalytic) …”
Section: The Preparation and Related Applications Of Lm Catalystsmentioning
confidence: 99%
“… LM catalysts for the chemical vapor deposition (CVD) growth of graphene. (a) 1–2 layers of graphene were grown on a LM (Ga) ball for 3–5 min; (b) growth of single‐layer, single‐crystalline graphene films on the LM (Ga) surface; (c) growth of graphene on different surfaces including liquid Ga, liquid In, and liquid Cu; (d) large area of graphene synthesized by Ga vapor‐assisted CVD; (e) growth of graphene on sapphire and polycarbonate by using liquid gallium (Ga) as catalyst; (f) synthesis of graphene on SiO 2 /Si substrates using Ga vapor catalyst; (g) graphene was grown at the interface between LM (Ga) catalyst and sapphire substrate under methane gas; (h) graphene grown at the interface between carbon film and LM (Ga) catalyst ,…”
Section: The Preparation and Related Applications Of Lm Catalystsmentioning
confidence: 99%
“…The perfectly smooth liquid surface supports uniform nucleation and growth of graphene. The growth of graphene governed by a self-limited surface catalytic process and is robust to variations in CVD growth conditions [89,90]. Homogenous monolayer graphene growth on liquid metals has been achieved using the CVD process.…”
Section: Liquid Metal Catalystmentioning
confidence: 99%